A Comparison of Two Operation Methods Revealed the Risk Factors and the Necessity of LN-prRLN Dissection in Papillary Thyroid Carcinoma: A Retrospective Cohort Study in FUSCC. (10th September 2020) - Wang, Yunjun; Wang, Dezhi; Chen, Lili; Guo, Kai; Sun, Tuanqi
Abstract : Background . Although the American Thyroid Association (ATA) guidelines indicate that central lymph nodes posterior to the right recurrent laryngeal nerve (LN-prRLN) should be routinely dissected, pr-RLN dissection is often neglected due to the high risk of injury to the recurrent laryngeal nerve (RLN). The purpose of this study was to investigate the risk factors associated with LN-prRLN metastasis in patients with papillary thyroid carcinoma (PTC) by preoperative examination and the indications for LN-prRLN dissection. Methods . A total of 1487 consecutive patients with PTC who underwent total thyroidectomy or right lobectomy plus isthmic resection with central LN dissection (CLND) were divided into two groups: patients with LN-prRLN dissection (group A) and patients without LN-prRLN dissection (group B). Clinicopathologic data were reviewed of the patients who were operated on by the same thyroid surgery team in the Department of Head Neck Surgery, Fudan University Shanghai Cancer Center (FUSCC) between August 2011 and May 2019. The relationships of LN-prRLN metastasis with clinicopathologic characteristics were analyzed by univariate and multivariate logistic regression. Results . The incidence of LN-prRLN metastasis was 34.1% (129/378). Univariate analysis showed that sex (P ≤ 0.001 ), tumor size (P ≤ 0.001 ), extrathyroidal extension (P = 0.002 ), concurrent Hashimoto's thyroiditis (P = 0.009 ), cLNMa (central lymph nodes anterior to the right recurrent laryngeal nerve) (P ≤ 0.001 ), cLNMa number (P ≤ 0.001 ), and lateral LN metastasis (LLNM) (P ≤ 0.001 ) were significantly associated with LN-prRLN metastasis in PTC. Multivariate logistic regression analysis revealed that tumor size (P = 0.039 ), cLNMa (P = 0.001 ), and LLNM (P = 0.025 ) were independent risk factors for LN-prRLN metastasis in patients with PTC. Although there was no significant difference between the two groups in recurrence, we found that 4 cases relapsed in the LN-prRLN compartment in group B, while none relapsed in group A. Conclusion . LN-prRLN metastasis is often identified in patients with PTC. Patients with large tumor sizes, cLNMa and LLNM are at a high risk of LN-prRLN metastasis and should be recommended for careful LN-prRLN dissection.